combination of PhP typing and β-d-glucuronidase gene sequence variation analysis for differentiation of Escherichia coli from humans and animals - Masters, N; Christie, M; Katouli, M; Stratton, H (Canadian journal of microbiology, 2015)
We investigated the usefulness of the β-d-glucuronidase gene variance in Escherichia coli as a microbial source tracking tool using a novel algorithm for comparison of sequences from a prescreened set of host-specific isolates using a high-resolution PhP typing method. A total of 65 common biochemical phenotypes belonging to 318 E. coli strains isolated from humans and domestic and wild animals were analysed for nucleotide variations at 10 loci along a 518 bp fragment of the 1812 bp β-d-glucuronidase gene. Neighbour-joining analysis of loci variations revealed 86 (76.8%) human isolates and 91.2% of animal isolates were correctly identified. Pairwise hierarchical clustering improved assignment; where 92 (82.1%) human and 204 (99%) animal strains were assigned to their respective cluster. Our data show that initial typing of isolates and selection of common types from different hosts prior to analysis of the β-d-glucuronidase gene sequence improves source identification. We also concluded that numerical profiling of the nucleotide variations can be used as a valuable approach to differentiate human from animal E. coli. This study signifies the usefulness of the β-d-glucuronidase gene as a marker for differentiating human faecal pollution from animal sources.